An overview of proteomic methods for the study of ‘cytokine storms’ - David, Paul; Hansen, Frederik; Bhat, Adil; Weber, Georg (Expert Review of Proteomics, 2021)
Introduction: The cytokine storm is a form of excessive systemic inflammatory reaction triggered by a myriad of factors that may lead to multi-organ failure, and finally to death. The cytokine storm can occur in a number of infectious and noninfectious diseases including COVID-19, sepsis, ebola, avian influenza, and graft versus host disease, or during the severe inflammatory response syndrome. Area covered: This review mainly focuses on the most common and well-known methods of protein studies (PAGE, SDS-PAGE, and high- performance liquid chromatography). It also discusses other modern technologies in proteomics like mass spectrometry, soft ionization techniques, cytometric bead assays, and the next generation of microarrays that have been used to get an in-depth understanding of the pathomechanisms involved during the cytokine storm. Expert opinion: Overactivation of leukocytes drives the production and secretion of inflammatory cytokines fueling the cytokine storm. These events lead to a systemic hyper-inflammation, circulatory collapse and shock, and finally to multiorgan failure. Therefore, monitoring the patient’s systemic cytokine levels with proteomic technologies that are redundant, economical, and require minimal sample volume for real-time assessment might help in a better clinical evaluation and management of critically ill patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: COVID-19; Cytokine storm; immunoassays; immunotherapies; mass spectrometry; proteomic methods

CD71 expressing circulating neutrophils serve as a novel prognostic biomarker for metastatic spread and reduced outcome in pancreatic ductal adenocarcinoma patients - Hansen, Frederik; Mittelstädt, Anke; Clausen, Finn-Niklas; Knoedler, Samuel; Knoedler, Leonard; Klöckner, Sebastian; Kuchenreuther, Isabelle; Mazurie de Keroualin, Johanne; Arnold, Lisa-Sophie; Anthuber, Anna; Jacobsen, Anne; Merkel, Susanne; et al. (Scientific Reports, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies, presenting a persisting global health burden. Neutrophils have a double-edged role in tumor progression exhibiting both pro-tumor and anti-tumor functions. CD71, also known as transferrin receptor 1, performs a critical role in cellular iron uptake and is highly expressed on proliferating cells, and especially on activated immune cells. CD71 is known to be elevated in various types of solid cancers and is associated with poor prognosis, however, the expression of CD71 on neutrophils in PDAC and its potential clinical impact is still unknown. Therefore, we analyzed CD71 on circulating neutrophils in PDAC and clinical control patients and found a significant increased expression in PDAC patients. High expression of CD71 on neutrophils in PDAC patients was associated with reduced outcome compared to low expression. CD71 on neutrophils correlated positively with the levels of proinflammatory cytokines IL-6, IFN-γ, and growth factor ligands CD40-L, and BAFF in plasma of PDAC patients. Finally, we have demonstrated that high expression of CD71 on neutrophils was also associated with an increased expression of CD39 and CD25 on circulating T-cells. Based on our findings, we hypothesize that CD71 on neutrophils is associated with tumor progression in PDAC. Further studies are required to investigate the distinct functionality of CD71 expressing neutrophils and their potential clinical application.
CRIS-Team Scopus Importer:2024-09-20
Keywords: CD71; Metastatic spread; Neutrophils; Pancreatic ductal adenocarcinoma; Prognostic biomarker; Transferrin receptor 1

Circulating Monocytes Serve as Novel Prognostic Biomarker in Pancreatic Ductal Adenocarcinoma Patients - Hansen, Frederik; David, Paul; Akram, Marina; Knoedler, Samuel; Mittelstädt, Anke; Merkel, Susanne; Podolska, Malgorzata; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; Kouhestani, Dina; Anthuber, Anna; et al. (Cancers, 2023)
Pancreatic ductal adenocarcinoma (PDAC) ranks among the most fatal cancer diseases, widely accepted to have the most dismal prognoses. Although immunotherapy has broadly revolutionized cancer treatment, its value in PDAC appears to be relatively low. Exhibiting protumoral effects, monocytes have recently been proposed as potential targets of such immunotherapeutic regimens. However, to date, the body of evidence on monocytes’ role in PDAC is scarce. Therefore, we analyzed monocytes in the peripheral blood of 58 PDAC patients prior to surgery and compared them to healthy individuals. PDAC patients showed increased levels of monocytes when compared to healthy controls In addition, patients with perineural infiltration demonstrated a higher percentage of monocytes compared to non-infiltrating tumors and PDAC G3 was associated with higher monocyte levels than PDAC G2. Patients with monocyte levels > 5% were found to have an 8.9-fold increased risk for a G3 and perineural infiltrated PDAC resulting in poorer survival compared to patients with <5% monocyte levels. Furthermore, PDAC patients showed increased expressions of CD86 and CD11c and decreased expressions of PD-L1 on monocytes compared to healthy individuals. Finally, levels of monocytes correlated positively with concentrations of IL-6 and TNF-α in plasma of PDAC patients. Based on our findings, we propose monocytes as a novel prognostic biomarker. Large-scale studies are needed to further decipher the role of monocytes in PDAC and investigate their potential as therapeutic targets.
CRIS-Team Scopus Importer:2023-02-03
Keywords: grading; liquid biopsy; monocytes; pancreatic ductal adenocarcinoma; perineural invasion; prognostic biomarker

Electrochemiluminescence in paired signal electrode (ECLipse) enables modular and scalable biosensing - Cho, Young Kwan; Kim, Hyunho; Benard, Alan; Woo, Hyun Kyung; Czubayko, Franziska; David, Paul; Hansen, Frederik; Lee, Jong Ik; Park, Jay Hoon; Schneck, Emmanuel; Weber, Georg; Shin, Ik Soo; et al. (Science Advances, 2022)
Electrochemiluminescence (ECL) has an inherently low background and enables precise chemical reactions through electrical control. Here, we report an advanced ECL system, termed ECLipse (ECL in paired signal electrode). We physically separated ECL generation from target detection: These two processes were carried out in isolated chambers and coupled through an electrode. The strategy allowed us to minimize cross-chemical reactions, design electrodes for high ECL signals, and integrate multiple sensors in a chip. As a proof of concept, we implemented an eight-plex ECLipse and applied it to detect host factors in human plasma. ECLipse achieved higher signal-to-noise ratio than conventional ECL assays and was >7000-fold more sensitive than enzyme-linked immunosorbent assay. In a pilot clinical study, we could detect septic conditions by measuring host factors [i.e., interleukin-3 (IL-3), IL-6, and procalcitonin (PCT)]. ECLipse assay further revealed distinct IL-3 and IL-6 patterns in patients with severe acute respiratory syndrome coronavirus 2 infection.
CRIS-Team Scopus Importer:2022-09-30

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

Gynecomastia Surgery in 4996 Male Patients Over 14 Years: A Retrospective Analysis of Surgical Trends, Predictive Risk Factors, and Short-Term Outcomes - Knoedler, Leonard; Knoedler, Samuel; Alfertshofer, Michael; Hansen, Frederik; Schenck, Thilo; Sofo, Giuseppe; Obed, Doha; Hollmann, Katharina; Siegwart, Laura C.; Vollbach, Felix H.; Bigdeli, Amir K.; Kauke-Navarro, Martin; et al. (Aesthetic Plastic Surgery, 2024)
Background: The high prevalence of benign male breast tissue enlargement (gynecomastia) has resulted in a marked increase of gynecomastia cases. While about one third of male adults experience some form of gynecomastia, gynecomastia surgery (GS) outcome research is limited to small study populations and single-center/-surgeon databases. In this study, we aimed to access the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database to identify preoperative risk factors for complications and investigate postoperative outcomes of GS. Methods: In this retrospective study, we queried the ACS-NSQIP database from 2008 to 2021 to identify male adult patients who underwent GS. Postoperative outcomes involved the occurrence of any, surgical and medical complications, as well as reoperation, readmission, and mortality within a 30-day postoperative time period. Univariable and multivariable assessment were performed to identify risk factors for complications while adjusting for possible confounders. Results: The study included 4,996 GS patients with a mean age of 33.7 ± 15 years and BMI of 28.2 ± 5.1 kg/m2. White patients constituted 54% (n = 2713) of the cohort, and 27% (n = 1346) were obese. Except for 2020, there was a steady increase in GS cases over the study period. Outpatient surgeries were most common at 95% (n = 4730), while general surgeons performed the majority of GS (n = 3580; 72%). Postoperatively, 91% (n = 4538) of patients were discharged home; 4.4% (n = 222) experienced any complications. Multivariable analysis identified inpatient setting (p < 0.001), BMI (p = 0.023), prior sepsis (p = 0.018), and bleeding disorders (p = 0.047) as independent risk factors for complications. Conclusion: In this study, we analyzed 4996 male adult GS patients from the ACS-NSQIP database, revealing an increased caseload and significant general surgeon involvement. Risk factors like bleeding disorders, inpatient status, and prior sepsis were linked to postoperative complications, while BMI was crucial for predicting adverse events. Overall, our findings may aid in enhancing patient care through advanced preoperative screening and closer perioperative management. Level of Evidence III: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
CRIS-Team Scopus Importer:2024-06-21
Keywords: ACS-NSQIP; Big data database; Gynecomastia; Gynecomastia surgery; Male breast enlargement; Risk factors

Impact of sarcopenia on outcomes in surgical patients: a systematic review and meta-analysis - Knoedler, Samuel; Schliermann, Rainer; Knoedler, Leonard; Wu, Mengfan; Hansen, Frederik; Matar, Dany Y.; Obed, Doha; Vervoort, Dominique; Haug, Valentin; Hundeshagen, Gabriel; Paik, Angie; Kauke-Navarro, Martin; et al. (International Journal of Surgery, 2023)
BACKGROUND: Surgeons have historically used age as a preoperative predictor of postoperative outcomes. Sarcopenia, the loss of skeletal muscle mass due to disease or biological age, has been proposed as a more accurate risk predictor. The prognostic value of sarcopenia assessment in surgical patients remains poorly understood. Therefore, the authors aimed to synthesize the available literature and investigate the impact of sarcopenia on perioperative and postoperative outcomes across all surgical specialties. METHODS: The authors systematically assessed the prognostic value of sarcopenia on postoperative outcomes by conducting a systematic review and meta-analysis according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, searching the PubMed/MEDLINE and EMBASE databases from inception to 1st October 2022. Their primary outcomes were complication occurrence, mortality, length of operation and hospital stay, discharge to home, and postdischarge survival rate at 1, 3, and 5 years. Subgroup analysis was performed by stratifying complications according to the Clavien-Dindo classification system. Sensitivity analysis was performed by focusing on studies with an oncological, cardiovascular, emergency, or transplant surgery population and on those of higher quality or prospective study design. RESULTS: A total of 294 studies comprising 97 643 patients, of which 33 070 had sarcopenia, were included in our analysis. Sarcopenia was associated with significantly poorer postoperative outcomes, including greater mortality, complication occurrence, length of hospital stay, and lower rates of discharge to home (all P <0.00001). A significantly lower survival rate in patients with sarcopenia was noted at 1, 3, and 5 years (all P <0.00001) after surgery. Subgroup analysis confirmed higher rates of complications and mortality in oncological (both P <0.00001), cardiovascular (both P <0.00001), and emergency ( P =0.03 and P =0.04, respectively) patients with sarcopenia. In the transplant surgery cohort, mortality was significantly higher in patients with sarcopenia ( P <0.00001). Among all patients undergoing surgery for inflammatory bowel disease, the frequency of complications was significantly increased among sarcopenic patients ( P =0.007). Sensitivity analysis based on higher quality studies and prospective studies showed that sarcopenia remained a significant predictor of mortality and complication occurrence (all P <0.00001). CONCLUSION: Sarcopenia is a significant predictor of poorer outcomes in surgical patients. Preoperative assessment of sarcopenia can help surgeons identify patients at risk, critically balance eligibility, and refine perioperative management. Large-scale studies are required to further validate the importance of sarcopenia as a prognostic indicator of perioperative risk, especially in surgical subspecialties.
CRIS-Team Scopus Importer:2024-12-16

Interleukin-3 protects against viral pneumonia in sepsis by enhancing plasmacytoid dendritic cell recruitment into the lungs and T cell priming - Benard, Alan; Hansen, Frederik; Uhle, Florian; Klösch, Bettina; Czubayko, Franziska; Mittelstädt, Anke; Jacobsen, Anne; David, Paul; Podolska, Malgorzata; Anthuber, Anna; Swierzy, Izabela; Schaack, Dominik; et al. (Frontiers in Immunology, 2023)
Rationale: Sepsis, a global health burden, is often complicated by viral infections leading to increased long-term morbidity and mortality. Interleukin-3 (IL-3) has been identified as an important mediator amplifying acute inflammation in sepsis; however, its function in the host response to viral infections during sepsis remains elusive. Objectives: To investigate the role of IL-3 during viral pneumonia in sepsis. Methods: We included septic patients from two different cohorts and used in vitro and in vivo assays. The obtained data were substantiated using a second model (SARS-CoV-2 infections). Measurements and main results: Low plasma IL-3 levels were associated with increased herpes simplex virus (HSV) airway infections in septic patients, resulting in reduced overall survival. Likewise, Il-3-deficient septic mice were more susceptible to pulmonary HSV-1 infection and exhibited higher pulmonary inflammation than control mice. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating plasmacytoid dendritic cells (pDCs) into the airways and by enhancing pDC-mediated T cell activation upon viral stimulation. Interestingly, the ability of IL-3 to improve adaptive immunity was confirmed in patients with SARS-CoV-2 infections. Conclusion: Our study identifies IL-3 as a predictive disease marker for viral reactivation in sepsis and reveals that IL-3 improves antiviral immunity by enhancing the recruitment and the function of pDCs.
CRIS-Team Scopus Importer:2023-03-24
Keywords: interleukin-3; plasmacytoid dendritic cells; sepsis; T cell priming; viral pneumonia

Surgical Management of Breast Capsular Contracture—A Multi-institutional Data Analysis of Risk Factors for Early Complications - Knoedler, Samuel; Knoedler, Leonard; Boroumand, Sam; Alfertshofer, Michael; Diatta, Fortunay; Sofo, Giuseppe; Huelsboemer, Lioba; Hansen, Frederik; Könneker, Sören; Kim, Bong Sung; Perozzo, Filippo A.G.; Ayyala, Haripriya; et al. (Aesthetic Plastic Surgery, 2024)
Background: Capsular contracture (CC) is a common complication following implant-based breast surgery, often requiring surgical intervention. Yet, little is known about risk factors and outcomes following CC surgery. Methods: We reviewed the American College of Surgeons National Surgical Quality Improvement Program database (2008–2021) to identify female patients diagnosed with CC and treated surgically. Outcomes of interest included the incidence of surgical and medical complications at 30-days, reoperations, and readmissions. Confounder-adjusted multivariable analyses were performed to establish risk factors. Results: 5,057 patients with CC were identified (mean age: 55 ± 12 years and mean body mass index [BMI]: 26 ± 6 kg/m2). While 2,841 (65%) women underwent capsulectomy, capsulotomy was performed in 742 patients (15%). Implant removal and replacement were recorded in 1,160 (23%) and 315 (6.2%) cases, respectively. 319 (6.3%) patients experienced postoperative complications, with 155 (3.1%) reoperations and 99 (2.0%) readmissions. While surgical adverse events were recorded in 139 (2.7%) cases, 86 (1.7%) medical complications occurred during the 30 day follow-up. In multivariate analyses, increased BMI (OR: 1.04; p = 0.009), preoperative diagnosis of hypertension (OR: 1.48; p = 0.004), and inpatient setting (OR: 4.15; p < 0.001) were identified as risk factors of complication occurrence. Conclusion: Based on 14 years of multi-institutional data, we calculated a net 30 day complication rate of 6.3% after the surgical treatment of CC. We identified higher BMI, hypertension, and inpatient setting as independent risk factors of postoperative complications. Plastic surgeons may wish to integrate these findings into their perioperative workflows, thus optimizing patient counseling and determining candidates’ eligibility for CC surgery. Level of Evidence III: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
CRIS-Team Scopus Importer:2024-07-05
Keywords: ACS-NSQIP; Breast implant; Breast surgery; Capsular contracture; Capsular fibrosis

The Multifaceted Functionality of Plasmacytoid Dendritic Cells in Gastrointestinal Cancers: A Potential Therapeutic Target? - Hansen, Frederik; David, Paul; Weber, Georg (Cancers, 2024)
Gastrointestinal (GI) tumors pose a significant global health burden, necessitating the exploration of novel therapeutic approaches. Plasmacytoid dendritic cells (pDCs) play a crucial role in tumor immunity, exhibiting both anti-tumor and pro-tumor effects. This review aims to summarize the role of pDCs in different types of GI tumors and assess their potential as therapeutic targets. In gastric cancer, hepatocellular carcinoma, and intrahepatic cholangiocarcinoma, increased infiltration of pDCs was associated with a worse outcome, whereas in esophageal cancer, pancreatic cancer, and colorectal cancer, pDC infiltration improved the outcome. Initial animal studies of gastric cancer and hepatocellular carcinoma showed that pDCs could be a successful therapeutic target. In conclusion, pDCs play a multifaceted role in GI tumors, influencing both anti-tumor immunity and tumor progression. Further research is needed to optimize their clinical application and explore combinatorial approaches.
CRIS-Team Scopus Importer:2024-07-12
Keywords: cholangiocarcinoma; colorectal cancer; esophageal cancer; gastric cancer; hepatocellular carcinoma; pancreatic cancer; pDCs; plasmacytoid dendritic cells

Tumor Infiltration with CD20+CD73+ B Cells Correlates with Better Outcome in Colorectal Cancer - Hansen, Frederik; Wu, Zhiyuan; David, Paul; Mittelstädt, Anke; Jacobsen, Anne; Podolska, Malgorzata; Ubieta Hernández, Kenia; Brunner, Maximilian; Kouhestani, Dina; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Immunotherapy has become increasingly important in the treatment of colorectal cancer (CRC). Currently, CD73, also known as ecto-5′-nucleotidase (NT5E), has gained considerable interest as a potential therapeutic target. CD73 is one of the key enzymes catalyzing the conversion of extracellular ATP into adenosine, which in turn exerts potent immune suppressive effects. However, the role of CD73 expression on various cell types within the CRC tumor microenvironment remains unresolved. The expression of CD73 on various cell types has been described recently, but the role of CD73 on B-cells in CRC remains unclear. Therefore, we analyzed CD73 on B-cells, especially on tumor-infiltrating B-cells, in paired tumor and adjacent normal tissue samples from 62 eligible CRC patients. The highest expression of CD73 on tumor-infiltrating B-cells was identified on classswitched memory B-cells, followed by naive B-cells, whereas no CD73 expression was observed on plasmablasts. Clinicopathological correlation analysis revealed that higher CD73+ B-cells infiltration in the CRC tumors was associated with better overall survival. Moreover, metastasized patients showed a significantly decreased number of tumor-infiltrating CD73+ B-cells. Finally, neoadjuvant therapy correlated with reduced CD73+ B-cell numbers and CD73 expression on B-cells in the CRC tumors. As promising new immune therapies are being developed, the role of CD73+ B-cells and their subsets in the development of colorectal cancer should be further explored to find new therapeutic options.
CRIS-Team Scopus Importer:2022-05-20
Keywords: B-cells; CD20; CD73; colorectal cancer; neoadjuvant treatment